2018
DOI: 10.37134/jcit.vol8.3.2018
|View full text |Cite
|
Sign up to set email alerts
|

Performance Based Pay Management as a Determinant of Procedural Justice

Abstract: The main objective of this study is to examine the relationship between performance based pay management (i.e., communication and participation) and procedural justice. A survey methods were used to collect selfreport survey of employees in currier service company. The SmartPLS path model analysis revealed two main findings: first, communication was significantly correlated with procedural justice. Second, participation was significantly correlated with procedural justice. These findings demonstrate that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Highlighting the importance of teacher job satisfaction is essential for cultivating educators' dedication to producing outstanding students. Individuals facing elevated expectations in their work environment tend to experience heightened levels of satisfaction, positively influencing the overall work process (Abd Razak et al, 2018). According to Hamali (2016), job satisfaction serves as an indicator of positive emotions in an individual, representing their value in the workforce through the work environment factor.…”
Section: The Relationship Between Job Satisfaction and Work Productivitymentioning
confidence: 99%
“…Highlighting the importance of teacher job satisfaction is essential for cultivating educators' dedication to producing outstanding students. Individuals facing elevated expectations in their work environment tend to experience heightened levels of satisfaction, positively influencing the overall work process (Abd Razak et al, 2018). According to Hamali (2016), job satisfaction serves as an indicator of positive emotions in an individual, representing their value in the workforce through the work environment factor.…”
Section: The Relationship Between Job Satisfaction and Work Productivitymentioning
confidence: 99%
“…Whereas, for the organization that operates in the global market with high competition, they are more likely to choose a merit-based pay system. Within this pay system, the amount, type, and level of pay is determined based on a worker's productivity (Abd Razak et al, 2018;Harada, 2019). In-depth analysis of the literature has revealed that there are two dimensions of merit-based pay.…”
Section: Introductionmentioning
confidence: 99%
“…Amalan pendekatan ini dilihat lebih kompetitif kerana ia dapat menarik, mengekal dan memotivasikan pekerja yang kompeten dan berprestasi tinggi untuk kekal bersama organisasi (Alhajjar et al, 2018;Azman & Ridwan, 2017;Ganesh, 2016). Natijahnya, keadaan ini akan merangsang peningkatan produktiviti dan daya saing organisasi di peringkat tempatan dan antarabangsa (Ismail & Razak, 2017b;Razak et al, 2018).…”
unclassified